Antioxidant Molecules Isolated from Edible Prostrate Knotweed: Rational Derivatization to Produce More Potent Molecules. (27th February 2022) - Mahnashi, Mater H.; Alyami, Bandar A.; Alqahtani, Yahya S.; Alqarni, Ali O.; Jan, Muhammad Saeed; Hussain, Fida; Zafar, Rehman; Rashid, Umer; Abbas, Muhammad; Tariq, Muhammad; Sadiq, Abdul
Abstract : Prostrate knotweed also called Polygonum aviculare is an important edible plant. The polygonum is majorly known for the phenolics and antioxidants. The antioxidants combat the excessive free radicals within the body. The excessive free radicals are implicated in various other diseases like diabetes, Alzheimer's, and inflammation. This study was aimed at exploring the antioxidant bioactives and their derivatizations to produce new molecules with advanced pharmacological features. We have isolated six compounds (1–6 ) from Polygonum aviculare . Furthermore, rational-based chemical derivatives for compound 5 have been formed for the management of diabetes, Alzheimer's, and inflammation. In preliminary antioxidant studies, all the isolated compounds (1–6 ) showed potential results against DPPH and ABTS free radicals. Based on the IC50 and chemical nature of the compounds, compound 5 was subjected to derivatization. Keeping the phenolic part of compound 5 unaffected, hydroxy succinimide (5A ) and thiazolidinedione (5B ) were synthesized. The compound 5A was found to be a potent inhibitor of AChE, BChE, COX-1, COX-2, 5-LOX, and DPPH giving IC50 values of 10.60, 15.10, 13.91, 1.08, 0.71, and 1.05 μ M, respectively. The COX-2 selectivity of compound 5A was found at 12.9. The compound 5B was found to be a potent multitarget antidiabetic agent giving IC50 values of 15.34, 21.83, 53.28, and 1.94 μ M against α -glucosidase, α -amylase, protein tyrosine phosphatase 1B, and DPPH. Docking studies were performed to manipulate the binding interactions. The docking pose of all the tested compounds was found to have increased binding affinity against all tested targets that supported the in vitro results. Our results showed that Polygonum aviculare is a rich source of antioxidant compounds. The two new derivatives have enhanced pharmacological features to treat diabetes, inflammation, and Alzheimer's disease.